Challenges of Teaching English for Elementary School Student in Indonesian Rural Areas - Fitri Nur Laila; Yeni Prastiwi; Endang Fauziati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Teaching English in rural areas presents another hurdle for English language teachers. Furthermore, this present study attempted to analyze the challenges of teaching English for young learners in Indonesian rural area. This study employed qualitative methodology and case study was used as a research design. Then, in this study, purposive sampling was adopted to select the participants. Furthermore, three elementary English teachers were participated as the participants in this study. In addition, the data were collected through semi-structured interview. Then, to validate the data this study used credibility, transferability, dependability, and confirmability. Furthermore, thematic analysis was used to analyse the data. This study discovered that there were five main challenges of teaching English in rural areas which were the status of English in curriculum, lack of qualified English teacher, insufficient of educational facilities, students’ negative attitudes toward English and students’ socio-economic background. Additionnally, the implications of this study was provided valuable information for further research and can be helpful to school's stakeholders to increase the quality of the education in the English language learning process, especially at the primary level of education.